Meneroka kesejahteraan psikologi dan kualiti pusat jagaan warga emas di Selangor - Nurhazirah Huda Nazali,; Khadijah Alavi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The services provided should address the needs of the elderly which include physical, social, psychological and emotional needs. This emphasized to ensure that senior citizens are able to live in a healthy environment. Therefore, this study was conducted qualitatively to explore the quality of services in aged care centers from a psychological and emotional perspective. The findings of the study identified the criteria that contribute to the quality of aged care center which are physical criteria, social environment criteria and mental health criteria; and based on the psychological and emotional well-being of the occupants. The quality of a good mental health in aged care center should meet all criteria in the psychological and emotional well-being of the resident. Collaboration between aged care center operators and professional in psychological field is also important to contribute improving the quality of aged care in the Malaysian elderly care industry.